1995
DOI: 10.1248/bpb.18.1396
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Constituents with Cytotoxic and Cytostatic Activity of Two Turkish Medicinal Plants Phlomis armeniaca and Scutellaria salviifolia.

Abstract: Ten known glycosidic compounds, betulalbuside A (1), 8-hydroxylinaloyl,3-O-beta-D-glucopyranoside (2) (monoterpen glycosides), ipolamide (3) (iridoid glycoside), acteoside (verbascoside) (4), leucosceptoside A (5), martynoside (6), forsythoside B (7), phlinoside B (8), phlinoside C (9), and teuerioside (10) (phenylpropanoid glycosides) were isolated from methanolic extracts of Phlomis armeniaca and Scutellaria salviifolia (Labiatae). Structure elucidations were carried out using 1H-, 13C-NMR and FAB-MS spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
2
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 0 publications
4
73
2
1
Order By: Relevance
“…It is noteworthy that this compound was isolated and identi®ed by our group from the titled plant as well as by Sudo et al at the same time from Premna subscandens as a new natural product (Sudo et al, 2000). Compounds 5±15 were identi®ed as follows: compound (5) auroside (C Ë alis et al, 1991), compound (6) lamiide (El-Naggar and Beal, 1980), compound (7) 8-epiloganin (Bianco and Passacantilli, 1981), compound (8) ipolamiide (Saracoglu et al, 1995), compound (9) syringin (Sugiyama et al, 1993), compound (10) (11) acteoside (Saracoglu et al, 1995), compound (12) chrysoeriol-7-O-b-glucopyranoside (Tomas et al, 1986), compound (13) acacetin-7-O-b-glucopyranoside (Harborne and Mabry, 1982), compound (14) luteolin-7-O-b-glucopyranoside (ElNegoumy et al, 1986) and compound (15) liriodendrin (Kamel et al, 1992). ow rate of mobile phase 6 ml/min, injection vol.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…It is noteworthy that this compound was isolated and identi®ed by our group from the titled plant as well as by Sudo et al at the same time from Premna subscandens as a new natural product (Sudo et al, 2000). Compounds 5±15 were identi®ed as follows: compound (5) auroside (C Ë alis et al, 1991), compound (6) lamiide (El-Naggar and Beal, 1980), compound (7) 8-epiloganin (Bianco and Passacantilli, 1981), compound (8) ipolamiide (Saracoglu et al, 1995), compound (9) syringin (Sugiyama et al, 1993), compound (10) (11) acteoside (Saracoglu et al, 1995), compound (12) chrysoeriol-7-O-b-glucopyranoside (Tomas et al, 1986), compound (13) acacetin-7-O-b-glucopyranoside (Harborne and Mabry, 1982), compound (14) luteolin-7-O-b-glucopyranoside (ElNegoumy et al, 1986) and compound (15) liriodendrin (Kamel et al, 1992). ow rate of mobile phase 6 ml/min, injection vol.…”
Section: Resultsmentioning
confidence: 83%
“…In Egyptian folk medicine, the plant is used as antidiabetic (Watt and Breyer, 1962). Dierent classes of glycosides comprising diterpenoids (Tanaka et al, 1983(Tanaka et al, , 1985Katagiri et al, 1994), iridoids (El-Naggar and Beal, 1980;C Ë alis et al, 1991), phenylpropanoids (C Ë alis et al, 1991;Saracoglu et al, 1995), phenylethanoids (Saracoglu et al, 1998) and avonoids (El-Negoumy et al, 1986;Tomas et al, 1986) had been identi®ed from genus Phlomis. Many of the phenylpropanoids isolated from genus Phlomis showed signi®cant biological activities, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several types of cancer cells are sensitive to the cytotoxic actions of caffeic acid-containing PhGs such as angoroside A, angoroside B, angoroside C, and poliumoside [195]. Further studies on SAR indicated that the o-dihydroxyl aromatic system within the molecule is necessary for these PhGs' cytotoxic and cytostatic activities [195].…”
Section: Cytotoxic and Antiproliferative Effectsmentioning
confidence: 99%
“…Further studies on SAR indicated that the o-dihydroxyl aromatic system within the molecule is necessary for these PhGs' cytotoxic and cytostatic activities [195]. In another study by Iida et al, poliumoside showed high inhibitory activity with IC 50 values ranging from 9 -42 μM against DNA polymerases, indicating the potential of using this compound as a lead candidate for the development of antitumor agent targeting DNA polymerases and/or HIV-1 reverse transcriptase [196].…”
Section: Cytotoxic and Antiproliferative Effectsmentioning
confidence: 99%